2000
DOI: 10.1210/en.141.10.3623
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Up-Regulates Expression of Orexin and Its Receptors in Rat Brain

Abstract: Orexins are two recently discovered neuropeptides that can stimulate food intake. As the chronic use of tobacco typically leads to a reduction in body weight, it is of interest to determine whether nicotine, the major biologically active tobacco ingredient, has an effect on orexin metabolism in the brain. Using a semiquantitative RT-PCR technique, the levels of messenger RNA (mRNA) for prepro-orexin, orexin A (OX1-R) and orexin B (OX2-R) receptors were 20-50% higher in rats receiving nicotine for 14 days at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 0 publications
4
62
0
1
Order By: Relevance
“…Previous research found that chronic nicotine modulates several neuropeptides such as neuropeptide Y (40), galanin (41), and orexins (42) in the hypothalamus or in the mesolimbocortical dopamine regions. However, it was unclear if chronic nicotine altered these peptides in the DS.…”
Section: Table I Changed Prohormone-derived Peptides and Unchanged Knmentioning
confidence: 99%
“…Previous research found that chronic nicotine modulates several neuropeptides such as neuropeptide Y (40), galanin (41), and orexins (42) in the hypothalamus or in the mesolimbocortical dopamine regions. However, it was unclear if chronic nicotine altered these peptides in the DS.…”
Section: Table I Changed Prohormone-derived Peptides and Unchanged Knmentioning
confidence: 99%
“…The rats quickly became tolerant to the dose, and no seizures were observed [24,36]. An initiation phase of 48 h was used to habituate the animals to the stress of the injection, as confirmed by reduction of c-fos expression [47].…”
Section: Animals Nicotine Administration and Brain Punchesmentioning
confidence: 99%
“…Many reports implicate nicotine as the appetite suppressing component of smoking (Grunberg, 1986;Blaha et al, 1998;Li et al, 2000;Zhang et al, 2001). Studies of feeding behavior reveal that smoking or nicotine administration decreases meal size, measured as the amount of food intake per meal, without substantial changes in meal number (Blaha et al, 1998;Miyata et al, 2001).…”
Section: Does Nicotine Affect Feeding Via Interactions At Peripheral mentioning
confidence: 99%